Nigella Sativa-mediated Synthesis of BiVO4/g-C3N4 Composites for the Removal of Methylene Blue Dye - Haryadinaru, Ghinatanitha Haqqu; Setyaningtyas, Tien; Riapanitra, Anung (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study investigates the synthesis and photocatalytic performance of BiVO4-Nigella Sativa/g-C3N4 composites for the degradation of methylene blue dye. The composites were synthesized using a coprecipitation method and characterized through various techniques, including X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), UV-Vis diffuse reflectance spectroscopy (DRS), Brunauer-Emmett-Teller (BET) surface area analysis, and scanning electron microscopy (SEM) to determine their crystal structure, chemical composition, morphology, adsorption and photocatalytic abilities. A variation of mass ratios of BiVO4 to g-C3N4 of 1:2, 1:3, and 1:4 was used in this investigation. The photocatalytic test results indicated that the composite with a mass ratio of 1:2 achieved the highest methylene blue degradation, reaching 91.73%, which was primarily attributed to an adsorption activity of 81.12% and a photocatalytic degradation of 10.60%. The photocatalytic activity was significantly enhanced under alkaline conditions, particularly at pH levels between 9 and 10, which facilitated the formation of reactive oxygen species (ROS). The study highlights the synergistic effects of the BiVO4 and g-C3N4 combination, which promotes efficient charge transfer, reduces electron-hole recombination, and expands light absorption due to a decrease in the effective bandgap energy. Overall, the findings indicate that BiVO4-Nigella Sativa/g-C3N4 composites have considerable potential for application in wastewater treatment, particularly for the remediation of organic dye pollutants. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).